ØªØ£Ø«ÙŠØ± ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ù‚ØµØ© Ø§Ù„Ù…Ù‚Ø·Ø¹ÙŠØ© (Strip Story) ÙÙŠ ØªØ±Ù‚ÙŠØ© Ø¥ØªÙ‚Ø§Ù† Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Wirdiatun Wizri wirdiatun; Ruwaida Hudatullah; Siti Rauhillah (Lughatu Ad-Dhat, 2022)
Among the many problems learning Arabic are the media, methods of learning Arabic, and enthusiasm for learning Arabic. In this university research, the researcher focused on the media, specifically through the use of the Strip story method, considering this method is suitable for learning vocabulary. The questions